Colistin-resistant Escherichia coli in calves and adult cattle from Portuguese dairy farms - Ribeiro, Madalena F.; Pinho, Luís; V. Brito, Nuno; Campos, Carla; Freitas, Ana R.; Quinteira, Sandra; Miranda, Carla (Scientific Letters, 2024)
Background: Antimicrobial resistance poses a pressing and significant challenge, driven by the intricate interplay among animals, humans, and the environment [1]. Escherichia coli, a commensal within animal and human gut microbiota, stands as one of the most ubiquitous bacteria. With a multitude of resistance genes, many E. coli strains exhibit a multidrug-resistant phenotype, diminishing the effectiveness of available antimicrobial agents [2] and becoming a major challenge in human therapeutics. Resistance to colistin, which is currently only used in humans as a last resort against multidrug-resistant bacteria [2,3], is unknown in fecal E. coli from Portuguese bovine. Objective: To detect E. coli carrying mobilized-colistin resistance (mcr) genes isolated from Portuguese dairy cattle. Methods: Fecal pools divided by age groups (8 adult or 8 calf samples) were collected from Holstein-Friesian dairy cattle produced on 8 farms in the Northern region (Braga and Porto), with a history of antibiotic administration in the last 3 months. Each farm comprised 2 pools totaling 128 samples (8 farms´16 pools). Samples were plated onto MacConkey agar (with or without 3 µg/mL colistin). Typical colonies from each plate were identified by MALDI-TOF MS and screened for mcr-1, mcr-2 and mcr-3 genes by PCR [3]. Results: Representative E. coli (n=26) identified in 15/16 pools (7 adults and 8 calves) were selected for mcr screening. The mcr-1 gene was detected in 46% (n=12) of the E. coli isolates from 11 positive pools (6 isolates from 6 calf pools and 6 isolates from 5 adult animal pools). In 5 farms, both age groups analyzed were positive. No mcr-2 and mcr-3 were identified. Conclusions: This study represents the first detection of the mcr-1 colistin-resistance gene in E. coli from dairy cattle, including calves, in Portugal. These highlight the potential public health risk posed by livestock as a reservoir and source of mcr-1genes able to reach humans through the food chain or the environment.